Prevalence and Factors Associated with Medical Unfitness among Seafarers in Thailand - Rakshit, Pornpidcha; Piemnithikul, Premyot (Journal of Preventive Medicine Association of Thailand, 2025)
Objective: To determine the prevalence and factors associated with medical unfitness among seafarers in Thailand. Methods: The study design was an analytical case-control study utilized secondary data from the online seafarer medical certificate database, which contains the results of seafarers’ medical fitness examination across Thailand. Data were collected from January 1, 2016 to December 31, 2024. The study sample consisted of 67 seafarers who failed (Case) and 201 seafarers who passed (Control) the medical fitness examination. Factors associated with medical unfitness were analyzed by multivariable logistic regression analysis and the prevalence of medical conditions contributing to medical unfitness was analyzed by proportion test. Results: The statistically significant factors associated with medical unfitness among seafarers were having a BMI in the obese range (³25.00 kg/m²), working in the engine department and serving on bulk carriers or tankers. Obesity was associated with medical unfitness, with an adjusted odds ratio of 2.96 (95% CI: 1.18 – 7.45) compared with normal weight. Employment in the engine department was associated with an adjusted odds ratio of 2.46 (95% CI: 1.24 – 4.85) relative to the deck department. Service on bulk carriers or tankers was associated with adjusted odds ratios of 8.79 (95% CI: 1.56 – 49.44) and 5.93 (95% CI: 1.67 – 21.01), respectively, compared with container ships. Diseases of the circulatory system were the leading cause of unfitness, accounting for 23.9% of cases. Conclusion: Factors associated with medical unfitness among seafarers are linked to work-related stress and unhealthy behaviors, leading to obesity, a major risk factor for cardiovascular diseases, the leading cause of medical unfitness. Therefore, health promotion should focus on lifestyle modification and dietary control, along with physical activity suited to the onboard environment and improvements in working conditions, workload and shift schedules.